Population Status of Primates in the Atlantic Forest of Argentina - Agostini, Ilaria (2015)
To guide future conservation actions and management decisions, it is crucial to assess the population status and identify the environmental or anthropogenic variables that affect species’ abundance and persistence. The main goal of our study was to evaluate the population and conservation status of the three primate species inhabiting the Atlantic Forest of Misiones, Argentina: the brown howler monkey (Alouatta guariba), the black-and-gold howler monkey (Alouatta caraya), and the black-horned capuchin monkey [Sapajus (= Cebus) nigritus]. We conducted repeated surveys at 31 transects in the central-eastern portion of Misiones province where the three species co-occur, and used occupancy models to assess the effect of human accessibility on black-horned capuchins. In addition, we carried out interviews with local people to assess the status of all three species and the extent to which yellow fever outbreaks may have affected each of them. During the surveys we found no direct or indirect evidence of the presence of brown howlers or black-and-gold howlers in the study area, while we recorded 18 direct and indirect signs of presence of black-horned capuchins in a total of 12 sites. Based on interviews and comparisons with previous density estimates, we conclude that the abundance of both howler species has dropped drastically, possibly due to recent yellow fever outbreaks. Conservation action is thus urgent, especially for the endangered brown howler population. Although black-horned capuchins are not currently considered threatened, we found them to be sensitive to anthropogenic disturbance. In the next few decades, the predictable spread and increasing intensity of human activities in this region may cause a drastic decline of this capuchin population.